Development of novel high performance asymmetric ultra low pressure nanofiltration (Aulp-NF) membrane for charged solutes removal - Abdul Rahman Hassan (Fakulti Sains dan Teknologi, 2011)
Nanofiltration is the most recently developed pressure-driven membrane process for the liquid-phase separations. As continuous developed of new membranes materials, special features likes nanometer ranges of pore radius, high retention of charged particles, inherent charges and lower operating pressure, its applications are rapidly increased especially in the field of process water, drinking water or wastewater treatment.